E-057 Embolization of a spinal dural AV fistula after super selective WADA test spinal AV fistula presenting as foot drop. (4th July 2012) - Nduku, V; Barrer, S; Shah, Q; Kozak, O; Yoon, M; Meagher, R; Gopez, J
Abstract : Spinal arteriovenous malformations are uncommon lesions that present with a constellation of nonspecific symptoms eluding most clinicians. They comprise 3%–16% of all compressive spinal cord lesions and are attributed to 30% of idiopathic myelopathies. They are most often diagnosed on imaging by a neuroradiologist. They can present with symptoms of myelopathy and radiculopathy mimicking a plethora of pathologies. We report the case of a 79-year-old female who presented with back pain and a left foot drop. MRI suggested edema in the conus medullaris and a spinal angiogram revealed serpiginous enhancement from T11-L1 consistent with a type I AVM (Dural AV fistula). She eventually underwent successful embolization after a super selective WADA test with complete occlusion of the Spinal AV fistula. Competing interests: None.